Human Immunodeficiency Virus Infection in Pregnancy - Yasemin Arikan; David R Burdge (Canadian Journal of Infectious Diseases)
The incidence and prevalence of human immunodeficiency virus (HIV) infection in women of child-bearing age continue to increase both internationally and in Canada. The care of HIV-infected pregnant women is complex, and multiple issues must be addressed, including the current and future health of the woman, minimization of the risk of maternal-infant HIV transmission, and maintenance of the well-being of the fetus and neonate. Vertical transmission of HIV can occur in utero, intrapartum and postpartum, but current evidence suggests that the majority of transmission occurs toward end of term, or during labour and delivery. Several maternal and obstetrical factors influence transmission rates, which can be reduced by optimal medical and obstetrical care. Zidovudine therapy has been demonstrated to reduce maternal-infant transmission significantly, but several issues, including the short and long term safety of antiretrovirals and the optimal use of combination antiretroviral therapy in pregnancy, remain to be defined. It is essential that health care workers providing care to these women fully understand the natural history of HIV disease in pregnancy, the factors that affect vertical transmission and the management issues during pregnancy. Close collaboration among a multidisciplinary team of knowledgeable health professionals and, most importantly, the woman herself can improve both maternal and infant outcomes.